A Critical Assessment of Teaching and Learning Experiences During the Era of The Covid-19 Pandemic: A Case Study - Zuana, Muhammad Mujtaba Mitra (Majapahit Journal of English Studies, 2023)
The slow spread of Covid-19 was a big problem for the school system. This made a lot of experts want to look into cases from the time. But it’s unlikely that many studies have been done on how teaching and learning go in a classroom where phones are used. A classroom where phones are used as the main learning tool is called a phone-infused classroom. The goal of this study is to find out how people think about and use phones in the classroom. Three English teachers and 66 children at the Islamic Elementary School in Mojokerto were asked to fill out questionnaires and talk with a focus group. The researcher looked at the transcript and gave a qualitative descriptive study of the results. As a result of the research, three themes came to light: the effects on teaching practices, teachers’ and students' strengths and challenges, and teachers' and students' evaluations of worth. Overall, the use of phones in teaching and learning during the pandemic era has had both good and negative effects. Lastly, education during an outbreak must be seen as a community effort by the government, teachers, parents, and schools to improve the effectiveness of teaching and learning methods that use cell phones that have been hurt by the outbreak and make sure that students don't fall behind.